In-Service Training Needs of Efl Teachers in Non-Formal Education Settings - Sezen Arslan; İsmail Hakkı Mirici; Hüseyin Öz (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
The education system in Turkey consists of the implementations in both formal and non-formal education settings; however, the majority of studies related to educational practices and teacher education focus on formal education settings. For this reason, this study aims to investigate the professional training needs of English as a foreign language (EFL) teachers in non-formal education settings. With this in mind, a non-formal education (NFE) institution in İstanbul was chosen since it had a high course attendee capacity and 105 EFL teachers who taught at this institution attended in the study. A needs analysis questionnaire and a semi-structured interview were used to collect the data about the training needs of the participants. The findings revealed that the needs centered around skills, vocabulary instruction, teaching pronunciation, material development, use of instructional technology in ELT, teaching mixed-ability classes, and classroom management. Findings also revealed that the teachers had a desire to improve their speaking skills through the in-service teacher training (INSET) programs.